2015
DOI: 10.1001/jamainternmed.2015.0157
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Published Scientific Evidence on Glycemic Control in Adult Intensive Care Units

Abstract: IMPORTANCE Little is known about the deadoption of ineffective or harmful clinical practices. A large clinical trial (the Normoglycemia in Intensive Care Evaluation and Survival Using Glucose Algorithm Regulation [NICE-SUGAR] trial) demonstrated that strict blood glucose control (tight glycemic control) in patients admitted to adult intensive care units (ICUs) should be deadopted; however, it is unknown whether deadoption occurred and how it compared with the initial adoption. OBJECTIVE To evaluate glycemic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 43 publications
2
73
0
7
Order By: Relevance
“…Local stakeholders (patient, family, physician, and consultant) and global stakeholders (industry, regulators, academics, and the public) interact in complex ways (social media, literature, lay press, guidelines, advertising, formularies, package inserts, and direct interaction) to generate choices based on a variety of inputs (indication, feasibility, preference, and cost) (11)(12)(13)(14)(15)(16). Because of this complexity, actual practice can be characterized only empirically, answering questions such as what treatment choices are being made in clinical practice, how many patients experience which combination of therapies, and how patterns may change over time or across different locations and practice types.…”
mentioning
confidence: 99%
“…Local stakeholders (patient, family, physician, and consultant) and global stakeholders (industry, regulators, academics, and the public) interact in complex ways (social media, literature, lay press, guidelines, advertising, formularies, package inserts, and direct interaction) to generate choices based on a variety of inputs (indication, feasibility, preference, and cost) (11)(12)(13)(14)(15)(16). Because of this complexity, actual practice can be characterized only empirically, answering questions such as what treatment choices are being made in clinical practice, how many patients experience which combination of therapies, and how patterns may change over time or across different locations and practice types.…”
mentioning
confidence: 99%
“…In contrast, data comparing PPIs with H2RAs in terms of their association with nosocomial pneumonia are conflicting. Although several metaanalyses comparing PPIs and H2RAs showed no difference in the rate of nosocomial pneumonia, [5][6][7] several large observational studies have suggested an increased risk of pneumonia with PPIs relative to H2RAs. 15,16 Similarly, although observational studies have suggested an association between the use of PPIs and C. difficile-associated diarrhea, 14,17 the risk of this problem with use of H2RA appears to be lower.…”
Section: Point Counterpoint Should We Continue To Use Stress Ulcer Prmentioning
confidence: 99%
“…With the subsequent introduction of proton pump inhibitors (PPIs) came small trials comparing the efficacy of these newer and more potent agents with that of the H2RAs. Several meta-analyses have suggested increased efficacy with PPIs relative to H2RAs for stress ulcer prophylaxis, [5][6][7] but these analyses comprised poor-quality trials that included patients with variable risk of stress ulcers and assessed different outcomes (overt versus clinically important bleeding). The trials varied in sample size from 28 to 359 patients, and were underpowered relative to the landmark Cook trial (n = 1200 patients).…”
Section: Point Counterpoint Should We Continue To Use Stress Ulcer Prmentioning
confidence: 99%
See 1 more Smart Citation
“…Yatak başında iyi klinik uygulamalar, etkinliği kanıtlanmış uygulamaların benimsenmesi kadar zararlı olduğu gösterilmiş uygulamaların da terk edilmesini gerektirir (1). Yapılan çalışmalar sağlık bakım sistemlerinin, klinik uygulamalarda yayınlanmış bilimsel kanıtları kullanmakta yetersiz kaldığını göstermektedir.…”
Section: Introductionunclassified